Moderate-Intensity Exercise and Musical Co-Treatment Decreased the Circulating Level of Betatrophin - Hendra Susanto; Ahmad Taufiq; Sugiharto; Desiana Merawati; Khumaira Marsyidah Badu; Jerry Dwi Trijoyo Purnomo; Adeodatus Yuda Handaya (International Journal of Endocrinology)
Introduction. In general, the significant contribution of lack of physical activity is strongly correlated with lipid metabolism and metabolic disorder. Hitherto, betatrophin is a potential hormone that regulates the lipid profile in the body circulation-associated triglyceride level. This study was designed to evaluate the alteration of betatrophin levels in subject-onset hypertriglyceridemia with exercise intervention co-treated with music. Materials and Methods. A total of 60 nonprofessional athletes were enrolled in this study and given moderate-intensity exercise (MIE) combined with middle rhythm musical co-treatment. The ELISA method was applied to quantify the serum level of betatrophin in all samples. The statistical analysis was performed by applying the Kolmogorov–Smirnov normality test, one-way ANOVA, and parametric linear correlation and regression. Results. Interestingly, our data show that MIE decreased the circulating level of betatrophin combined with music (12.47 ± 0.40 ng/mL) compared with that without musical co-treatment (20.81 ± 1.16 ng/mL) and high-intensity exercise (26.91 ± 2.23 ng/mL). The plasma level of betatrophin was positively correlated with triglycerides (r = 0.316, p≤0.05), systolic blood pressure (r = 0.428, p≤0.01), HDL (r = 0.366, p≤0.05), energy expenditure (r = 0.586, p≤0.001), PGC-1α (r = 0.573, p≤0.001), and irisin (r = 0.863, p≤0.001). By contrast, the plasma level of betatrophin was negatively associated with age (r = −0.298, p≤0.05) and LDL cholesterol (r = −0.372, p≤0.05). Importantly, betatrophin is a significant predictor for energy expenditure (p≤0.001) and plasma triglyceride levels (p≤0.05). Conclusions. Our data demonstrate that betatrophin levels decreased the post-MIE and musical therapeutical combination. Therefore, betatrophin may provide a benefit as the potential biomarker of physiological performance-associated physical training.